Pengaruh Kepemilikan Institusional, Likuiditas, Dan Pertumbuhan Perusahaan Terhadap Kebijakan Utang - Andri Zuda Abdurrahman; Erinos N.R; Salma Taqwa (Jurnal Eksplorasi Akuntansi, 2019)
This study aims to find empirical evidence regarding the relationship between institutional ownership, liquidity, company growth towards the company's debt policy. The population in this study were 41 mining companies listed on the Stock Exchange in 2015-2017, with the number of samples used was 38 companies. Data used was secondary data in the form of annual reports obtained from the IDX website (www.idx.co.id). Testing in this study was carried out by multiple linear regression analysis. The results show that institutional ownership has no effect on debt policy, liquidity has a negative effect on debt policy and the company's growth has an effect on debt policy